Diagnóstico de leucosis enzootica bovina en la hoya de Loja en hembras mayores a dos años, por medio del método de Elisa - Apolo Carrión, Janeth Karolina (2014)
This work in the Hoya de Loja, showed that the disease bovine leukosis is present. In a prevalence rate of 4.5%, the aim was to diagnose the presence of enzootic bovine leukosis (LEB ) by ELISA and blood count . 150 blood samples obtained from cattle herds in the Hoya de Loja were examined, the samples were taken in vacutainer tubes with anticoagulant jugular vein (150 samples ) and without anticoagulant ( 150 samples ) were transferred on dry ice to the laboratory Integral diagnosis Race Vet Veterinary Medicine , National University of Loja. Positive tests by Elisa method were found in the South and North of the Hoya de Loja sectors blood count and the percentages of lymphocytes were seen in the infected animals having a little marked elevation in terms of normal lymphocyte (40-70 %) for cattle